Analisis Interferensi dalam Kelas Kata Keishiki Meishi Khususnya Penggunaan Tame Ni dan You Ni - Novianti, Nalti; Dewi, Is Anggara (Bina Nusantara University, 2008)
Article aimed to find out the amount of interference in the translation using tame ni and you ni. The research used analysis description. Data were taken by giving a test to 20 student from the Japanese Department, Bina Nusantara University. The result showed that there is some interference in the exercises in the test given to the respondents. It is concluded that the interference occurs because many students do not understand the differences in using tame ni anda you ni.